GOOD CORPORATE GOVERNANCE DALAM SEKTOR PERBANKAN: ANALISIS IMPLEMENTASI BERDASARKAN KEBIJAKAN BI - Nurdhiana; Triani; Yuniarningtyas (Jurnal Akuntansi dan Bisnis, 2025)
This research aims to analyze the implementation of Good Corporate Governance at Bank BNI KK Pandanaran Semarang. The population in this study was all staff of the Internal Supervisory Unit (SPI) of Bank BNI KK Pandanaran Semarang, totaling 32 people. Data were analyzed using the Dean J. Champion formula. The results of the research show that overall Good Corporate Governance at Bank BNI KK Pandanaran Semarang has been implemented well. The principles of Accountability and Fairness have been implemented very well. The principles of Transparency, Independence and Accountability have been implemented well.